Pedagogical impact of integration of musculoskeletal anatomy blended learning on physiotherapy education - Delafontaine, Arnaud; Saiydoun, Gabriel; Frigout, Jérôme; Fabeck, Laurent; Degrenne, Olivier; Sarhan, François-Régis (Frontiers in Medicine, 2023)
Background In physiotherapy education, blended learning is recognized to be more effective compared to traditional teaching. The aim of this study was to assess the consequences of a musculoskeletal anatomy blended learning program on skills developed by students. Methods We conducted an observational retrospective monocentric study in a French physiotherapy school named “X.” Ninety-two first-year students in the 2017–18 baseline group (students with traditional face-to-face learning), and ninety-eight first-year students and ninety-five second-year students in the 2018–19 and 2019–20 blended learning experimental groups was included. A success rate of the anatomy final written exam, defined by the percentage of students scoring 50% or above, was analyzed between 2017 and 2020. We also evaluated the pedagogical value of musculoskeletal e-learning and its usefulness for preparing the student for their anatomy final written exam at «X». Results We observed an improvement in the success rate of the anatomy final written exam between the 2017–18 baseline group, 2018–19 and 2019–2020 experimental groups during first (Kruskal–Wallis = 74.06, df = 2, p < 0.001) and second semester (Kruskal–Wallis = 173.6, df = 2, p < 0.001). We obtained a data survey and questionnaire response rate of 74% (n = 89/120) for the 2018–19 and 62% (n = 72/116) for the 2019–20 experimental groups. Concerning questionnaire response, they were no significant statistical difference between 2018–19 and 2019–20 experimental groups. Conclusion Blended learning could improve student success rate of the anatomy final written exam and learning of professional physiotherapy skills.